1993
DOI: 10.21000/jasmr93010284
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Pyrite Morphology of Materials Separated from Coa

Abstract: Abstract.Flyash, scrubber sludge, gob, and slurry are materials separated during the washing and burning of coal at the Associated Electric power plant at Thomas Hill, Missouri. Each material was sampled at several time periods during summer, fall and winter of 1990. The samples were analyzed for 30 elements and X-ray diffraction patterns were run to indicate mineralogical composition. Pyrite concentration of the residues was determined by the H202 oxidation method. Pyrites were separated from the samples by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Nevertheless data are needed to evaluate the role of O 2 released from the roots of aquatic plants, growing in the wetlands, in pyrite oxidation. Zhang et al 159 employing microelectrodes, measured the rhizosphere pH and redox potential (Eh) of a pyrite soil in a wetland with cattail (Typha latifolia L.). They found that (1) the rhizosphere pH was one unit lower than the bulk soil pH, (2) the oxidation potential and sulfate concentration of the rhizosphere were higher than in bulk soil, and (3).…”
Section: A Inundation Of Pyritic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless data are needed to evaluate the role of O 2 released from the roots of aquatic plants, growing in the wetlands, in pyrite oxidation. Zhang et al 159 employing microelectrodes, measured the rhizosphere pH and redox potential (Eh) of a pyrite soil in a wetland with cattail (Typha latifolia L.). They found that (1) the rhizosphere pH was one unit lower than the bulk soil pH, (2) the oxidation potential and sulfate concentration of the rhizosphere were higher than in bulk soil, and (3).…”
Section: A Inundation Of Pyritic Materialsmentioning
confidence: 99%
“…They also reported that the conglomerates were the predominant form. Zhang et al 159 pyrite separated from scrubber sludge, gob, and slurry of coal residue. Their results indicated that scrubber sludge contained a trace amount of pyrite in the form of smooth-rounded, conglomerates, and framboidal forms.…”
Section: Introductionmentioning
confidence: 99%